CORPORATE DISCLOSURE : UPAYA MENGATASI ASIMETRI INFORMASI PEDAGANGAN ONLINE - Zakaria Ahmad, Maulana; Zainul Abidin, Ahmad; Ilma Ahmad, Zakiyyah; Wakhid, Abdul; Umam, Syafiul; Habibi, Rakhmawan (Universitas KH. A. Wahab Hasbullah, 2026)
Corporate Disclosure practices have become essential in addressing information asymmetry in online commerce. Corporate Disclosure enables companies to transparently and accountably reveal information about the products or services they offer, financial performance, business strategies, risks, and commitments to sustainability and social responsibility. By conducting proper and comprehensive Corporate Disclosure, companies provide greater access for buyers to obtain the information they need to make smart and informed purchasing decisions. This study aims to explore corporate disclosure practices in addressing information asymmetry within the online trading environment and to analyze their impact on mitigating information asymmetry risks. The research method used is a qualitative approach with a scoping review method, utilizing secondary data from relevant articles. The findings indicate that Corporate Disclosure is effective in creating a fairer, more transparent, and more sustainable business environment for all parties involved in online commerce. This article makes an important contribution to understanding the role of Corporate Disclosure in reducing information asymmetry in online trading. Recommendations are provided to business stakeholders, regulators, and academics to strengthen transparency and trust in online commerce through improved Corporate Disclosure practices.